Effects of alfentanil or fentanyl added to propofol for sedation in colonoscopy on cognitive functions: Randomized controlled trial - Güler Doğanay,; Perihan Ekmekçi,; Baturay Kansu Kazbek,; Hakan Yılmaz,; Gülbanu Erkan,; Filiz Tüzüner, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: To assess the effect of propofol supplemented with alfentanil or fentanyl on cognitive functions for sedation during elective colonoscopy.Materials and Methods: Patients (n=150, 18-65 years old, American Society of Anesthesiologists risk group I-III) scheduled undergo elective colonoscopy were included. They were randomized into three groups using the closed envelope methodpropofol-alfentanil (Group A), propofol-fentanyl (Group F), and propofol only (Group P).Group A patients were given an alfentanil (10 mcg/kg)-supplemented propofol bolus infusion and 5 mcg/kg alfentanil when necessary. Group F patients were given fentanyl (1 mcg/kg)-supplemented propofol and 0.5 mcg/kg fentanyl when necessary. Group P patients were given 1 mg/kg propofol and 0.5 mg/kg propofol when necessary. Vital signs, depth of sedation, recovery parameters, and patient and endoscopist satisfaction were recorded. Trieger dot test (TDT) and Digit Symbol Substitution Test (DSST) were performed post procedure.Results: Demographic data were similar among all patients in the groups. Bispectral index values were lower in Group P (p<0.001). DSST scores were higher in Group A (p=0.004). TDT scores and Facial Pain Scale scores were higher in Group P (p<0.005). Apnea incidence (p=0.009) and Observer’s Assessment of Alertness/Sedation Scale scores (p=0.002) were also higher in Group P. Patient satisfaction and endoscopist satisfaction were similar among all patients.Conclusions: Compared with propofol-alfentanil and propofol-fentanyl, propofol alone is associated with an increased incidence of apnea, drug consumption, and reported pain. Propofol-alfentanil has a less negative effect on cognitive functions than propofol alone or propofol-fentanyl.